Cannabis: a self‐medication drug for weight management? The never ending story. Issue 2 (12th October 2015) - Bersani, Francesco Saverio; Santacroce, Rita; Coviello, Marialuce; Imperatori, Claudio; Francesconi, Marta; Vicinanza, Roberto; Minichino, Amedeo; Corazza, Ornella
Abstract : In a society highly focused on physical appearance, people are increasingly using the so‐called performance and image‐enhancing drugs (PIEDs) or life‐style drugs as an easy way to control weight. Preliminary data from online sources (e.g. websites, drug forums, e‐newsletters) suggest an increased use of cannabis amongst the general population as a PIED due to its putative weight‐loss properties. The use of cannabis and/or cannabis‐related products to lose weight may represent a new substance‐use trend that should be carefully monitored and adequately investigated, especially in light of the well‐known adverse psychiatric and somatic effects of cannabis, its possible interaction with other medications/drugs and the unknown and potentially dangerous composition of synthetic cannabimimetics preparations. Abstract : Data from online sources suggest an increased use of cannabis amongst the general population as a "performance and image‐enhancing drug" due to its putative weight‐loss properties. The use of cannabis and/or cannabis‐related products to lose weight may represent a new substance‐use trend that should be carefully monitored and adequately investigated, especially in light of the well‐known adverse psychiatric and somatic effects of cannabis, its possible interaction with other medications/drugs and the potentially dangerous composition of synthetic cannabimimetics preparations.